Extracting Evaluation Factors of Social Resilience in Water Resource Protection Areas Using the Fuzzy Delphi Method - Huang, Ming-Feng; Peng, Li-Pei (Sustainability, 2023)
Development in water resource protection areas frequently grapples with balancing environmental sustainability and local economic growth. Consequently, a nuanced assessment of social resilience becomes imperative. This research presented a case study of the Water Resource Protection Area in Taipei, gauging its social resilience across five dimensions: “social support function”, “inclusive governance”, “economic allocation”, “built environment”, and “resources for sustainability”. From these, 49 influential factors that could impact the social resilience of the water resource protection area were discerned. Through the engagement of 21 experts via questionnaires and subsequent analysis using the Fuzzy Delphi method, this study identified 23 core factors. Notably, influential factors pertaining to the “social support function” significantly impacted the water resource protection area. The findings aim to streamline the evaluation of social resilience in water resource protection areas, potentially guiding future research utilizing the multi-criteria decision-making (MCDM) method and steering industrial developments in these areas.